Prevalence of depression and its association with sociodemographic factors in patients with chronic pain: A cross-sectional study in a tertiary care hospital in Saudi Arabia - Sameeh Al-Maharbi; Abdullah Bakr Abolkhair; Hani Al Ghamdi; Mamdouh Haddara; Yasser Tolba; Ahmed El Kabbani; Adwa Al Sadoun; Evelyn Pangilinan; Jaya Joy; Shadi Abu Khait; May Wathiq Al-Khudhairy (Saudi Journal of Anaesthesia, 2018)
Introduction: Mental health issues, especially depression, are common in chronic pain patients. Depression affects these patients negatively and could lead to poor control of their pain. Some risk factors for both chronic pain and depression are known and need to be targeted as part of the management in a multidisciplinary approach. This study was conducted to estimate the prevalence of depression among chronic pain patients attending a pain clinic and to explore the association between depression in chronic pain patients and other factors such as sociodemographic features, number of pain sites, severity of pain, and types of pain. Methods: This is a cross-sectional study that carried out in a chronic pain clinic in a tertiary care hospital in Riyadh, Saudi Arabia (King Faisal Specialist Hospital and Research Centre). All chronic pain patients including cancer-related pain, apart from acute pain patients and children, were eligible to participate in the study. Association between depression and sociodemographic factors was assessed with univariate and multivariate methods. Main outcome measures were the prevalence of depression in chronic pain patients using the Patient Health Questionnaire-9 (PHQ-9) and the association with sociodemographic factors. Results: A total of 200 chronic pain patients (128 females [64%]) participated in the study. The prevalence of depression was 71% (95% confidence interval: 64.7–77.3) based on the PHQ-9 diagnostic criteria using a cutoff point of >5. Among those patients who were depressed, 9 (4.5%) had severe depression as compared to 31 (15.5%), 41 (20.5%), and 61 (30.5%) who had moderately severe, moderate, and mild depression, respectively. Depression (scored at the cutoff point of 5) in chronic pain patients was significantly associated with age, financial status, medical history of depression, and pain severity. Conclusion: Depression is common among chronic pain patients with several risk factors aggravating its presentation. Due to their increased risk of depression, psychiatric counseling that offers mental health assistance should be prioritized and made available as a multidisciplinary approach for the treatment of chronic pain patients.